The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1128/iai.65.7.2707-2716.1997
|View full text |Cite
|
Sign up to set email alerts
|

Ribotypes and virulence gene polymorphisms suggest three distinct Listeria monocytogenes lineages with differences in pathogenic potential

Abstract: A total of 133 Listeria monocytogenes isolates were characterized by ribotyping and allelic analysis of the virulence genes hly, actA, and inlA to uncover linkages between independent phylogenetic and specific virulence markers. PCR-restriction fragment length polymorphisms revealed 8 hly, 11 inlA, and 2 actA alleles. The combination of these virulence gene alleles and ribotype patterns separated L. monocytogenes into three distinct lineages. While distinct hly and inlA alleles were generally found to cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
159
3
11

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(195 citation statements)
references
References 37 publications
20
159
3
11
Order By: Relevance
“…1). While previous studies have shown that isolates with three and four PRR are predominant in L. monocytogenes lineages I and II, respectively (Wiedmann et al, 1997), there were no significant associations between genetic lineage and number of PRRs among the isolates included in this study, supporting that this isolate set allows for comparisons of plaque size among isolates with three vs. four PRRs without lineage as a confounding factor. We thus conclude that the number of ActA PRRs is not associated with differences in plaque size among natural isolates, if isolates with three and four PRRs are equally represented within each lineage.…”
Section: Resultscontrasting
confidence: 57%
“…1). While previous studies have shown that isolates with three and four PRR are predominant in L. monocytogenes lineages I and II, respectively (Wiedmann et al, 1997), there were no significant associations between genetic lineage and number of PRRs among the isolates included in this study, supporting that this isolate set allows for comparisons of plaque size among isolates with three vs. four PRRs without lineage as a confounding factor. We thus conclude that the number of ActA PRRs is not associated with differences in plaque size among natural isolates, if isolates with three and four PRRs are equally represented within each lineage.…”
Section: Resultscontrasting
confidence: 57%
“…Restriction methods can be combined with PCR methods. PCR can be the first step, followed by restriction of the amplified product, as in hemolysin typing of Listeria monocytogenes [35] or PCR-RFLP of Cryptosporidium parvum [36]. Alternatively, restriction can be followed by PCR, as in amplified fragment length polymorphism typing.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Staphylococcus aureus in veterinary teaching hospitals [120] Identification of genetic determinants of disease and disease transmission Lineage-specific pathogenicity of Listeria monocytogenes in humans and ruminants [35] Confirmation of epidemiologically suspected transmission Transmission of Staphylococcus aureus mastitis by flies [121] Detection of epidemiologically unsuspected outbreaks…”
Section: Methicillin-resistantmentioning
confidence: 99%
“…As a species, L. monocytogenes is comprised of 13 serovars and at least two distinct genetic lineages (Piffaretti et al, 1989;Bibb et al, 1990;Ericsson et al, 2000;Call et al, 2003;Zhou et al, 2005). Serovars from one lineage (Division I; serovars 1/2b and 4b) have a greater predilection for causing disease in humans compared with serovars from the other lineage (Division II; serovars 1/2a and 1/2c) (Wiedmann et al, 1997).…”
Section: Introductionmentioning
confidence: 99%